Occurrence of Fusarium Wilt of Tomato under Protected Conditions in Himachal Pradesh, India - Bharat, Narender K.; Sharma, Jitender (International Journal of Bio-resource and Stress Management, 2023)
A survey of different polyhouses in tomato growing areas in Solan, Sirmour, Hamirpur and Bilaspur districts of Himachal Pradesh, India was carried out to record the incidence of Fusarium wilt during September, 2012. Overall incidence of Fusarium wilt in four districts surveyed was 19.50%. Amongst various localities surveyed highest incidence of the wilt was recorded at Kadriyana (27.65%) in district Hamirpur followed by Nauni (25.56%) in district Solan, whereas lowest incidence was recorded at Dharot (9.90%) in district Hamirpur followed by Gassour (12.50%) in district Bilaspur. Locality wise data indicated that the incidence of wilt was higher in comparatively warmer areas and also in the areas where tomato cultivation was continuously done under polyhouses. The wilt incidence at locations in warmer regions in all the districts surveyed was 20% and above. Previously no survey of the polyhouses in Himachal Pradesh has been done to know the status of Fusarium wilt, because of non occurrence or less incidence of the disease in the region. Hence, the present study is new in this regard. Isolation of the pathogen associated with tomato wilt was made from the diseased tissues in roots and collar region of the plant on the potato dextrose agar (PDA) medium. The pathogen thus isolated was identified to be Fusarium oxysporum f. sp. lycopersici (Sacc.) W.C. Snyder and H.N. Hans on the basis of its colony morphology and microscopic features. The pathogenecity of the fungal pathogen was also proved after artificial inoculation of the tomato seedlings.